Crop-livestock integration in Brazilian lands - Castagnara, Deise Dalazen; Garcez, Kelli Flores; Unamuzaga, Luiza Vandrielli Goulart; Schneider, Cibele Regina; Mattei, Eloisa; Ramão, Édipo Alex Malavolta; Valença, Gabriela Maidana; Bragança, Lueli Fernandes; Ramão, Cleiton José; Krolow, Rodrigo Holz; de Oliveira, Paulo Sérgio Rabello; Pintanel, Jackson Brazil Acosta (Seven Editora, 2024)
Integrated agricultural production systems (SIPA’s) consist of growing grain-producing crops with forage crops in the same area, in rotation, succession or intercropping. These systems, in addition to diversifying agricultural production, promote efficiency and sustainability in rural production, benefiting crops and livestock, are more sustainable, economically viable agricultural practices aimed at soil conservation. As, among the objectives of integrated systems, when well managed, they are capable of promoting improvements in soil quality, nutrient cycling, environmental adequacy and economic viability of the activities involved. As a result, the Integrated Crop-Livestock (ICL) system becomes a very important method, because it seeks to renew soil conditions, in order to make the most of natural processes, avoiding using external inputs. The ICL system is a viable alternative in edaphoclimatic conditions, there are many potentialities of the systems, enabling an increase in productivity and reduction of expenses for irrigation, fertilizers, soil conditioners and other agricultural inputs, integrating production, environmental conservation and socioeconomic benefits. DOI:https://doi.org/10.56238/sevened2024.023-029